2006
DOI: 10.1093/brain/awl205
|View full text |Cite
|
Sign up to set email alerts
|

TGF-  and metalloproteinases differentially suppress NKG2D ligand surface expression on malignant glioma cells

Abstract: NKG2D ligands (NKG2DL) are expressed by infected and transformed cells. They transmit danger signals to NKG2D-expressing immune cells, leading to lysis of NKG2DL-expressing cells. We here report that the NKG2DL MHC class I-chain-related molecules A and B (MICA/B) and UL16-binding proteins (ULBP) 1-3 are expressed in human brain tumours in vivo, while expression levels are low or undetectable in normal brain. MICA and ULBP2 expression decrease with increasing WHO grade of malignancy, while MICB and ULBP1 are ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
163
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(173 citation statements)
references
References 53 publications
9
163
1
Order By: Relevance
“…The paradoxical roles of this cytokine are highlighted in the results presented in this article. Thus, previous works have reported that TGF-b downregulates the expression of NKG2D and its ligands in different tumor types (32)(33)(34). In contrast, our experiments demonstrate that EMT of spontaneously immortalized nonmalignant keratinocytes (HaCaT cells) driven by this cytokine clearly results in a marked increase of NKG2DL expression.…”
Section: Discussioncontrasting
confidence: 55%
“…The paradoxical roles of this cytokine are highlighted in the results presented in this article. Thus, previous works have reported that TGF-b downregulates the expression of NKG2D and its ligands in different tumor types (32)(33)(34). In contrast, our experiments demonstrate that EMT of spontaneously immortalized nonmalignant keratinocytes (HaCaT cells) driven by this cytokine clearly results in a marked increase of NKG2DL expression.…”
Section: Discussioncontrasting
confidence: 55%
“…20 Suppressive cytokines (such as transforming growth factor (TGF)-b and IL-10) and regulatory T (Treg) cells within tumor microenvironments have been shown to suppress NKG2D and NKp30 expression on NK or CD8 1 T cells and also reduce MICA and ULBP expression on malignant cells. [46][47][48] These cytokines and Treg cells strongly contribute to the tumor's escape from NK cell-mediated anti-tumor immune response.…”
Section: Nk Receptors In Tumorsmentioning
confidence: 99%
“…This lack of efficacy might be related to immune inhibitory properties of glioblastoma cells facilitating immune evasion (Heimberger and Sampson, 2011). Glioma cells should per se be prone to attack by immune effector cells since they express ligands for activating immune receptors on NK cells or cytotoxic T cells (Dietrich et al, 2011;Eisele et al, 2006;Friese et al, 2003;Friese et al, 2004;Wischhusen et al, 2005). However, an immunosuppressive micromilieu hampers an efficient immune response.…”
Section: Introductionmentioning
confidence: 99%